Perancangan Aplikasi Absensi Karyawan Berbasis Mobile (Studi Kasus: PT. IPMS Bandung) - Nirmala, Selvia; Supendi, Kiki (SATIN - Sains dan Teknologi Informasi, 2024)
In the digital era, system-based technology becomes the primary key to enhancing human resource management efficiency. PT. IPMS Bandung addressed the challenges of managing employee attendance through research that designed an Android-based mobile attendance application as an efficient solution to the inefficient manual attendance process. This application was developed using the waterfall model. The result is an application that not only facilitates employees but also makes a positive contribution to operational efficiency and employee attendance data management at PT. IPMS Bandung. By utilizing Android technology and MySQL as the underlying data platform, this application is expected to be an adoptable solution by similar companies, enhancing employee productivity, and bringing significant improvements in attendance management in the workplace.